Analysis of affecting factors export volume and competitiveness of Indonesian palm oil (Crude Palm Oil) - Vini Anzani; Wiludjeng Roessali; Migie Handayani (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
Production of palm oil, especially crude palm oil (CPO) is increasing along with the increase in the number of oil palm plantations. The global market demand for this product has also increased its exports and competitiveness. This study aims (I) to analyze the development of Indonesia's CPO export volume in the period 2000 to 2020 (II) to analyze the factors that affect Indonesia's CPO export volume and (III) to analyze the competitiveness of Indonesia's CPO with Malaysia. The research was conducted in December 2021-February 2022. The research method used was descriptive quantitative method. The type of data used is secondary data in the form of time series for the period 2000-2020. The data used consists of CPO export volume, CPO production volume, international CPO price, sunflower seed oil price, CPO export value and Indonesian export value, CPO export value and Malaysian export value as well as CPO export value and world export value. Data sources were obtained from BPS, World Bank, International Monetary Fund, and FAO. The results showed that the percentage growth of Indonesia's CPO export volume in 2000-2020 was 7% with a percentage growth of 12% export value, simultaneously Indonesia's CPO export volume was influenced by factors of CPO production volume, international CPO prices and sunflower seed oil prices which had an effect real and significant. The volume of CPO production and international CPO prices partially have a real and significant effect on the volume of CPO exports, while the price of sunflower seed oil has no partial effect on the volume of CPO exports. The average RCA index for Malaysia was 2.17 and Indonesia was 2.12, which shows that Malaysia has a competitive advantage and higher CPO export competitiveness than Indonesia.